Dual role of pinostrobin-a flavonoid nutraceutical as an efflux pump inhibitor and antibiofilm agent to mitigate food borne pathogens1. Issue 76 (19th August 2015) - Christena, Lowrence Rene; Subramaniam, Shankar; Vidhyalakshmi, Mohan; Mahadevan, Vijayalakshmi; Sivasubramanian, Aravind; Nagarajan, Saisubramanian
<x xml:space="preserve">Abstract</x> Drastic 128 fold MIC reversal in MRSA stain via EPI effect. Remarkable anti-biofilm effect against gram negative bacteria. Efflux pump other than NorA is involved.